MENCARI KEBENARAN MATERIIL DALAM “HARD CASE” PENCURIAN TIGA BUAH KAKAO - Widodo Dwi Putro (Komisi Yudisial RI, 2010)
ABSTRACTLegal certainly and justice are two values that are often persevere in the formulation of the judge's decisions. This is more prominent, when judges face cases categorized as